The Intensification of Heat and Mass Transfer Processes in the Operating Condition of Automatic Fire Extinguishing Systems at Objects of Power; European Physical Journal Web of Conferences (EPJ Web of Conferences); Vol. 110 : Thermophysical Basis of Energy Technologies - Vysokomornaya O. V. Olga Valeryevna; Kopylov N. P. Nikolay; Lyrshchikov S. Yu. Sergey Yurievich; Dmitrienko M. A. Margarita Aleksandrovna (2016, 2016)
Title screen